2019
DOI: 10.1002/da.22972
|View full text |Cite
|
Sign up to set email alerts
|

Network analyses reveal which symptoms improve (or not) following an Internet intervention (Deprexis) for depression

Abstract: Background: Depression is a heterogeneous collection of symptoms. Prior metaanalyses using symptom sum scores have shown the Internet intervention, Deprexis, to be an efficacious treatment for depression. However, no prior research has investigated how Deprexis (or any other Internet intervention for depression) impacts specific symptoms of depression. The current study utilizes symptom-level analyses to examine which symptoms are directly, indirectly, or minimally influenced by treatment.Methods: Network anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This study aims to examine the change in structure of peripartum mental health from the network perspective. Using the network approach, we can go beyond merely looking at how the severity of depressive-anxiety symptoms change ( 20 ) as mothers transit from pregnancy to motherhood. In this study, we sought to study the reinforcing loops among symptoms, thus giving us insights into how the mechanisms of maternal mental health may change with the external circumstances ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to examine the change in structure of peripartum mental health from the network perspective. Using the network approach, we can go beyond merely looking at how the severity of depressive-anxiety symptoms change ( 20 ) as mothers transit from pregnancy to motherhood. In this study, we sought to study the reinforcing loops among symptoms, thus giving us insights into how the mechanisms of maternal mental health may change with the external circumstances ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by a recent meta-analysis of actigraphy data which found that depressed individuals were less active during the day and had longer awakenings in the middle of the night, but not a longer sleep latency, than healthy controls (Tazawa et al, 2019). Further, maintenance insomnia has been found to improve after an Internet-provided treatment for depression, whereas onset and terminal insomnia were not significantly changed (Mullarkey et al, 2020).…”
Section: Hypothesesmentioning
confidence: 81%
“…There were 542 participants who reported childhood trauma in baseline measurement and 294 completed all three measurements. Prior research has suggested that the imputation of missing data may introduce distortions in representing the relationships between variables (Borsboom et al, 2017; Mullarkey et al, 2020). As such, we included the 294 participants who completed all three measurements in our analysis.…”
Section: Methodsmentioning
confidence: 99%